The impacts of a biofuel use on the gas turbine operating performance - Febijanto, Irhan (Journal of Mechatronics, Electrical Power and Vehicular Technology, 2017)
The use of Pure Plant Oil (PPO) as a fuel blend in a power plant is mandatory as stipulated in the Ministerial Decree of Energy and Mineral Resource of the Republic of Indonesia. However, the implementation of PPO used in power generation has many obstacles due to a lack of information concerning the impacts of PPO used in the operating performance of the power generation engine. In this study, the effect of PPO as a blended fuel with High-Speed Diesel (HSD) was studied by using the gas turbine with a capacity of 18 MW. The PPO was blended based on volume with a ratio of 0%, 5%, 10% and 20%. As the results, it is shown that the use of PPO with a blend ratio of 20% is the maximum fuel blend ratio according to the threshold value of a flue gas temperature and a vibration velocity in the gas turbine.